Comparison of Early Inguinal Lymph Node Dissection and Neoadjuvant Chemotherapy in Penile Cancer Patient with Bulky Nodal Metastasis: A Cohort Study - Warli, Syah Mirsya; Ginting, Jeremy Thompson; Sihombing, Bungaran; Siregar, Ginanda Putra; Prapiska, Fauriski Febrian (Urology Journal, 2024)
Purpose: Penile cancer is a rare malignancy, where extranodal extension in inguinal or pelvic lymph nodes is associated with decreased 5-year cancer-survival rate in this study, we try to assess survival and quality of life in a penile cancer patient with bulky lymph node. Methods: We retrospectively reviewed data from penile cancer patients with bulky lymph nodes who underwent treatment between July 2016 and July 2021 at tertiary referral hospital care. The inclusion criteria (age >18 yr, histologically proven penile cancer, and completion of last treatment 6 months prior to this study) yielded a cohort of 20 eligible penile cancer patients with bulky lymph nodes (> 4 cm/bilateral mobile/unilateral fixed). Only patients who had completed therapy at least 6 months prior to the study were included. After obtaining consent, they were asked to complete the EORTC QLQ-C30 questionnaire to evaluate the patient's quality of life. Results: Out of 20 patients, 5 patients underwent direct ILND and 15 patients underwent chemotherapy. Median follow-up after primary diagnosis was 114+32 months in patients with early ILND and 52+11 months in patients who underwent delayed lymph node dissection. Out of 5 patients who underwent early ILND, all of them survived during follow-up, and achieved cancer-free status without residual tumor and with excellent functional outcomes (Karnofsky 90). There was no significant difference in social function (p-value = 0.551), physical function (p-value = 0.272), role function (p-value = 0.546), emotional function (p-value = 0.551), cognitive function (p-value = 0.453), and global health status (p-value = 0.893) between patient which treated with early ILND and Neoadjuvant Chemotherapy. However, patients who underwent early ILND showed a relatively better clinical outcome. Conclusion: Early ILND followed by adjuvant chemotherapy for penile cancer with palpable lymph nodes is more favourable than neoadjuvant TIP chemotherapy.